Financial risk mitigation of collateral-free kredit usaha rakyat mikro at Bank Syariah Indonesia KCP Ujung Berung 1 - Gustini, Yasni; Amaliah, Ima; Hartono, Budi (Journal of Islamic Economics Lariba, 2023)
IntroductionBank Syariah Indonesia participates in disbursing kredit usaha rakyat (KUR) mikro with a maximum financing ceiling of Rp 100 million without requiring collateral. This is worth further investigation, especially from the perspective of financing risk mitigation.ObjectivesThis research aims to identify risk mitigation strategies to reduce the impact on non-performing financings from kredit usaha rakyat mikro.MethodThe study is located at Bank Syariah Indonesia KCP Ujung Berung 1 in the city of Bandung, using a qualitative descriptive method. Research data is processed using interview and documentation techniques.ResultsField findings indicate dynamic disbursement of KUR from January to April, totaling Rp 3.69 million. In April 2023, delinquent credits decreased by 0.5% from 6.6% in March 2023 to 6.1%. This is evidenced by the risk mitigation strategy used to address delinquent credits, which involves identifying customers who meet established criteria and conducting necessary checks, such as BI checking/SLIK, trade checking, and market checking. Additionally, the bank requires customers to obtain life insurance before applying for financing.ImplicationsThe research motivates Islamic bank management to reduce financial risk in financing to micro, small, and medium enterprises by improving their financial risk mitigation.Originality/NoveltyThis study can serve as a reference for banks to reduce the risk of non-performing financing by implementing credit risk mitigation strategies.